A CASE OF SILENT SPONTANEOUS UTERINE RUPTURE AT 27-28 WEEKS OF GESTATION, TWO PRIOR C- SECTIONS AND HISTORY OF UTERINE RUPTURE - Lutfi, M.D.; Tengku Puspa Dewi (Universitas Syiah Kuala, 2018)
Introduction.Silent spontaneous rupture of the uterus at the second trimester of gestation was very rare. In this case was accompaniedby extrusion of an intact amniotic sac and normal fetal heart rate base line. Silent uterine rupture can be very difficult to diagnose, as the clinical features of uterine rupture, including abdominal pain, vaginal bleeding, maternal hypovolemic shock or hemorrhage, may be absent.Very few cases have been reported in literature.CasePresentation.Wereport a case of silent spontaneous uterine ruptureat 27-28 Weeks of Gestation.Patient had history of two prior cesarean sections with the last C-sections has uterine rupture. The residents were misdiagnosis silent spontaneous rupture with condition of dyspepsia. She underwent cesarean subtotal hysterectomy and deliveredalive infant. She had a good postoperative recovery and was discharged on postoperative day 3. Conclusion.Silent spontaneous rupture of the uterus at second trimester of gestation with extrusion of an intact amniotic sac is rare.For this case even there were no sign of acute abdomen and shock but only sign of dyspepsia. We have to think about the risk of Rupture uterine imminens. A high index of suspicion and good imagingduring pregnancy are important in making this diagnosis. Keywords: uterine rupture, dyspepsia, cesareanhysterectomy